Public Value under Chaotic Conditions - Friedrich, Peter; Eerma, Diana (Estonian Discussions on Economic Policy, 2018)
Economic interpretation of public value was elaborated in welfare theory and public choice literature. Nowadays public value describes the value that an organization contributes to society (Moore 1995). The authors discuss this definition and look for a more focused concept of value.The chaotic conditions can be defined according to chaos theory or as conditions of disorder. The authors show conditions for chaos’ situations. Even in situations that are characterized by deterministic model, the model solutions and public value may become unpredictable because of non-linear relations between variables or of initial conditions prevailing. Disorder situations occur in case of natural disasters, extreme population changes, economic crises, transformation situations and a breakdown of unions and national states. The difficulty to formulate public values are discussed for different kinds of disorders and evaluation schemes